Capability of arterial spin labeling MR imaging in localizing seizure focus in clinical seizure activity. Issue 7 (July 2016) - Kim, Beom Su; Lee, Soon-Tae; Yun, Tae Jin; Lee, Sang Kun; Paeng, Jin Chul; Jun, Jinsun; Kang, Koung Mi; Choi, Seung Hong; Kim, Ji-hoon; Sohn, Chul-Ho
Abstract: Purpose: The purpose of this study was to evaluate cerebral blood flow using arterial spin labeling (ASL) perfusion magnetic resonance (MR) imaging in patients with clinical seizure activity and determine its diagnostic performance in identifying seizure focus. Materials and methods: Institutional Review Board of our hospital approved this retrospective study. Informed consent was waived. Clinical seizure focus was determined by a neurologist based on seizure semiology, electroencephalography, and conventional imaging modalities. The diagnostic performance of ASL perfusion MR imaging to identifying seizure focus compared to clinical seizure focus was analyzed. Results: Clinical seizure focus was localized in 95% (42/44) of patients. The sensitivity and specificity of ASL perfusion MR imaging for identifying seizure focus were 74% (95% CI: 58%, 86%) (clinical seizure focus was localizable in 31 of 42 patients, including complete concordance in 10 patients and partial concordance in 21 patients) and 0% (95% CI: 0%, 84%) (for the two patients whose clinical seizure foci were not localizable, they were identified by ASL perfusion MR imaging), respectively. Thus, the overall accuracy of ASL perfusion MR imaging for localizing seizure focus was 70% (33/44). For 4 patients who had abnormal perfusion on ASL, their seizure foci based on ASL perfusion MR imaging were discordant with clinical seizure foci. Conclusion: ASL perfusion MR imaging can provide information about perfusion status and important diagnostic clue in localizing seizure focus in patients with clinical seizure activity. It has the potential as a non-invasive complementary diagnostic tool for patients with clinical seizure activity.